Tingkat Kebugaran Jasmani Mahasiswa Prodi Penjas Semester II Pada Fakultas Ilmu Pendidikan Universitas Muhammadiyah Mahakarya Aceh Takengon - Budiman Budiman; Ashari Efendi; Nopri Abadi Miko; Ahmadi Ahmadi (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2024)
This study aimed to determine the physical fitness level of Pshycal Education students at the Faculty of Education, University Muhammadiyah Mahakarya Aceh Takengon. The research used a descriptive approach and involved 21 students who participated in the study. The instrument used was the Bleep Test, which measures (VO2 Max) levels. The data analysis technique was descriptive, and the results showed that the students' endurance levels were relatively low, with the lowest score being 20.8 and the highest being 44.5. The findings suggest that more supervision and physical conditioning exercises are needed to improve the physical fitness of the students.